Beyond measure: using digital humanities to unravel the system of perspective within Japanese images in nara-ehon manuscripts of otogi-zōshi tales - Lagréou, Héléna D.M. (Eikón / Imago, 2024)
The present article illustrates the advantages of digital humanities to unearth new understandings, in this case of the Pre-Modern Japanese visual culture. Precisely, this article serves three purposes. Firstly, it is a guide to digital methods for size analysis in visual studies. Secondly, this study proposes a survey of the collection of nara-ehon manuscripts of yoko-hon format from the “Digital Collections of the Keio University Libraries”. Thirdly, I present my study of perspective in Pre-Modern Japanese images, which have been puzzling scholars. Indeed, the size of characters painted on the images varies greatly. Yet, these fluctuations in measurements are not used to illusorily transform a two-dimensional space into a three-dimensional one. The image composition and the varying sizes of characters do not create any spatial depth. Unfortunately, creating a systematic study of this visual conundrum was difficult prior to the rise of digital humanities, leaving researchers only with hypothesises. With these new creative methods, and the measurements of 1040 characters extracted from 244 images, the system of perspective within Japanese images is now clearer. Pre-Modern Japanese images use a psychological perspective intricately informed by a play on social norms restricted by the materiality of the manuscripts.